Editorial - Manjeet Singh Nain, (Indian Journal of Extension Education, 2022)
Editorial Organization for Economic Cooperation and Development (OCED) has projected that that global economy will take a bigger hit than previous forecast in 2023 amid the Russia- Ukraine conflict and projected at 2.2%. During 77th United Nations General Assembly, looming famine in Somalia and other African countries was discussed and in wake of the humanitarian crisis in the Horn needs to be at the top of the international agenda, and we need commitment, resources and action urgently. Simultaneously, Pakistan flooding shows 'adapting' to climate change can be a dangerous illusion as one third of the country is under water during September 2022. The recent United Nations climate report embraced supporting Indigenous self-determination, recognizing Indigenous Peoples’ rights and supporting Indigenous knowledge-based adaptation for reducing climate change risks and effective adaptation. Few of the manuscripts covered the pertinent question in current issue of the Indian Journal of Extension Education. It’s my privilege to present the current issue (October- December, 2022) containing 38 manuscripts from cross sectional authors and content ranging from basic research in the form of measuring tool development; use of multivariate typology livelihoods in climate sensitive agro-ecosystems; food and nutrition security of farm households; outlook of wheat and vegetable market; studies on producer federations;Impact of COVID-19 lockdown; value chain analysis; varietal preferences; social media predictors analysis; adoption studies; CHCs study; depredation by wild animals; CFLDs impact analysis; use of critical incident technique , ordinary least square method and ARIMA model for analysis; studies in fisheries science; efficacy on core life skills and MDP; dairy farming and milk consumption pattern; participatory seed production study:Constraints analysis in different settings, awareness and adoption studies; and role performance-expectation gap. During the quarter, with the inclusion in Index Copernicus International Journal Master list the IJEE is now getting wider circulation with the opportunity for citations and indexing. As on date indexed at CAB International; ICI; BASE; Google scholar; Scilit; Semantic Scholar; WorldCat; Science gate; Agricultural Science and Technology Information data base of FAO which has become possible by submitting metadata in desirable form to Crossref. The claim for inclusion in UGC CARE list has also been submitted. I extend my sincere thanks to all the authors for making valuable contributions. I also extend sincere thanks to all the expert members in the editorial board ( Himanshu K. De, Kalyan Ghadei, Rajeev Bairathi, S. S. Dolli & V.P.S. Yadav) for their painstaking efforts. The reviewers like Souvik Ghosh, Mahesh Chandra, P.K. Tiwari, Satyveer Meena, M.S. Meena and many other contributed a lot and deserve sincere thanks. I extend my sincere thanks to all the authors for making valuable contributions. The support extended by Executive Council is duly acknowledged. Special thanks are extended to the President, ISEE; Dr. U.S. Gautam, Secretary ISEE; Dr. Rashmi Singh, Treasurer, ISEE; Dr. B. K. Singh and Joint Secretary, ISEE; Dr. J. S. Malik for providing insightful thoughts and guidance in bringing out this issue. Dr. Bhanu P. Mishra, Vice President (Central Zone) deserves special thanks for making committed efforts at all stages of ISEE matters.(Manjeet Singh Nain)